Advanced driver assistance systems (ADAS): from safety regulation to metrology-driven calibration environments in the united states - Yurchylo, Roman (Global Prosperity, 2025)
Abstract. Federal safety rules, consumer safety rating schemes, and advancements in sensor tech have all contributed to the rapid implementation of Advanced Driver Assistance Systems (ADAS) in the US. However, while the benefits of these systems in reducing crash risks have been established, there is still a lack of scholarship on their impact on automotive diagnostics and service. Set against paradigms of service diagnostics based on measurement and component replacement, ADAS calibration is measurement-precise and critical. This paper contends that the process of ADAS calibration is overly reliant on the completion of steps, with little attention paid to the environment’s measurement and calibration. Variables such as floor structure, light level, light stability, and glare can all create blind spots in diagnostics and remain unnoticed. As such, even if calibration is said to be complete, there are likely to be shortcomings. To fill this gap, the paper proposes the first Yurchylo Calibration Environment Passport (YCEP), enacted through a YCEP Quick Test framework. YCEP converts qualitative criteria from workshops to quantitative, objective, and repetitive workshop criteria and applies to stationary and mobile ADAS calibration services to PASS/BORDER/FAIL decider logic. Based on the grounded theory of measurement science, the approach of the YCEP framework improves repeatability, lessens the need for rework, and heightens quality assurance to the U.S. automotive service ecosystem. The author states that environmental diagnostics are a necessity ADAS service quality improvement and will become a standard as systems become more complex and calibration sensitivities increase.